Phil Thornton on climate change adaptation and mitigation options for Africa - International Livestock Research Institute (International Livestock Research Institute, 2011)
Africa's agricultural sector experiences many of the impacts of climate change even though the continent is a minor contributor of greenhouse gases. African leaders and governments are part of on-going global initiatives (like the 2010 Cancun climate talks) to address climate change and many are putting in place measures to enable agricultural producers, especially small-scale farmers, adapt to already occurring climate change and deal with longer-term climate change challenges. Philip Thornton, an agricultural systems analyst with ILRI is interviewed by Australia's ABC NewsRadio.